DT-diaphorase triggered theranostic nanoparticles induce the self-burst of reactive oxygen species for tumor diagnosis and treatment. (15th April 2021) - Yan, Dan; Xu, Xiao; Ren, Chunling; Chen, Chen; Luo, Jianguang; Han, Chao; Kong, Lingyi
Abstract: On-demand therapy following effective tumor detection would considerably reduce the side effects of traditional chemotherapy. DT-diaphorase (DTD), whose level is strongly elevated in various tumors, is a cytosolic flavoenzyme that promotes intracellular reactive oxygen species (ROS) generation via the redox cycling of hydroquinones. Incorporation of the DTD-responsive substrate to the structures of the probe and prodrug may facilitate the tumor detection and therapy. Herein, we established an multifunctional drug delivery nanosystem (HTLAC) that rapidly responds to the DTD enzyme, leads to the early-stage precise detection and termination of tumors. Firstly, the synthesis of DTD-responsive withaferin A (DT-WA) and indocyanine green (DT-Cy5) was performed. In the presence of DTD, WA, which produces ROS in cells, was released from DT-WA, and the red fluorescence of DT-Cy5 was detected for tumor imaging. Additionally, these DTD enzyme reaction processes of DT-WA and DT-Cy5 induced ROS. The self-burst of ROS generation by the two enzyme reaction processes as well as the released WA then led to the apoptosis of tumor cells. To increase the bioavailability and tumor targeting of drugs, cell-penetrating peptide and hyaluronic acid functionalized liposomes were used to encapsulate the drugs. The detailed in vitro and in vivo assays showed that HTLAC achieved enhanced tumor detection and superior antitumor efficiency. According to above outcomes, results showed that HTLAC might provide an efficacious approach for the fabrication of enzyme-triggering nanosystems to detect tumor and induce the self-burst of ROS for an efficient tumor treatment. Statement of significance: We have fabricated a HTLAC nanosystem to address the need of bursting reactive oxygen species (ROS) generation within tumor site. Our goal uniquely aims at not only augmentation of ROS-inducing anticancer efficacy, but also to meet the challenges of tumor dynamic detection in the clinical practices. In this work, the DT-diaphorase responsive withaferin A (DT-WA) and indocyanine green (DT-Cy5) are synthesized, and observed more specifically toward DTD under physiological conditions. As the cell-penetrating peptide and hyaluronic acid functionalized liposome, the HTLAC not only induces antiproliferative activity by generating self-burst of ROS, but also effectively accumulate and restore its fluorescence at the tumor site because of the HA actively targeting tumor along with the prolonged presence in blood circulation. Besides, this enzyme-triggering nanosystem exhibited an effective tumor inhibition with a low systemic toxicity. Graphical abstract: Image, graphical abstract